Engaged Scholarship and Emancipation 75 Years of Cultural Anthropology and Development Studies at Radboud University - van Meijl, Toon; Wijsen, Frans (Radboud University Press, 2023)
This collective volume celebrates that 75 years ago the foundation was laid for the Department of Anthropology and Development Studies at Radboud University, Nijmegen, the Netherlands. The contributions to this volume exemplify the evolution of the academic disciplines of anthropology and development studies at Radboud University in the course of its history. Radboud University itself celebrates its centenary in the year 2023. Originally this university was established for the emancipation of the Catholic population in the Netherlands. Emancipation continues to be a distinctive feature of the university's policy, also of the scholarship as it is conducted in the department of anthropology and development studies. As emancipation and engagement are key concepts in the disciplines of anthropology and development studies at Radboud University, former and current staff members focus their contributions to this anniversary volume on the various meanings of the concepts of emancipation and engagement in their academic practices. They reflect on changes in the meaning of engaged scholarship in their own work, especially in relation to emancipatory issues. The outcome is a rich variety of contributions centering on the shifting tension between engagement and scholarship in the disciplines of anthropology and development studies. Thus, they not only exemplify the evolution of these academic disciplines at Radboud University, but also offer a topical and innovative perspective on a highly dynamic field.